Model‐Chain Validation for Estimating the Energy Yield of Bifacial Perovskite/Silicon Tandem Solar Cells. Issue 9 (23rd June 2022) - Tillmann, Peter; Jäger, Klaus; Karsenti, Asher; Kreinin, Lev; Becker, Christiane
Abstract : The power conversion efficiency of conventional silicon solar cells approaches its theoretical limit. Bifacial operation and the perovskite/silicon tandem device architecture are promising approaches for increasing the energy yield of photovoltaic modules. Here, an energy yield calculation tool for (bifacial) perovskite/silicon tandem solar cells is presented. It uses a chain of models for irradiance, optical absorption, and temperature‐dependent electrical performance. Each step is validated with irradiance and performance data from a rooftop installation with mono‐ and bifacial silicon solar cells in Jerusalem, Israel. Selecting the data for two days (one in summer, one in winter) and considering the high‐reflective ground of this particular installation (albedo 60%) a 20% increased energy yield for a bifacial module with respect to a monofacial module is modeled. This result matches well with experimental data. When "upgrading" the silicon solar cell to a perovskite/silicon tandem solar cell, the case study predicts up to 40% additional energy yield. Combining the concepts of bifacial solar operation and perovskite/silicon tandem solar cells results in up to 60% increased energy with a high albedo ground, and is therefore a promising approach to further decrease the levelized cost of electricity for photovoltaic electricity generation. Abstract : Energy yield (EY) estimation for various solar cell architectures using a combination of illumination, optical, and electrical models. With respect to a monofacial silicon solar cell, the EY of monofacial perovskite/silicon tandem solar cells increases by 42% and 43% for 2‐ and 4‐terminal configurations, and with bifacial operation by 55% and 61%, respectively.